Evaluation of the Iraqi Community for Election Campaigns for Candidates of the House of Representatives and Media Coverage in March 2010: (Cairo as a Model) - Al-Ameri, Muhammed Abd Hussein (ALBAHITH ALALAMI, 2013)
The elections of the Council of Representatives in Iraq are one of the manifestations of political participation, which makes it attracts the attention of researchers. Where Iraq witnessed in 2005 important political events in the Iraqi arena, a pluralist parliamentary elections or elections in Iraq by direct free election on January 30, the first almost half a century ago. On November 15 of the same year, Iraq adopted a permanent constitution for the country through a popular referendum.